2017
DOI: 10.22256/pubvet.v11n12.1263-1273
|View full text |Cite
|
Sign up to set email alerts
|

Electric energy generation and technical–economic viability of a biodigester in the hospital sector

Abstract: RESUMO.A construção de hospitais se transformou e evoluiu sensivelmente nas últimas décadas, sendo visto como um processo industrializado, com aumento em escala, o que gera grandes quantidades de resíduos, causando grandes problemas ambientais. Dentro deste contexto, faz-se necessária uma nova disposição para os resíduos produzidos (biomassa) e sua reutilização. Seguindo técnicas apropriadas, surge como opção o uso do biodigestor, o qual permite que os resíduos hospitalares sejam tratados podendo gerar energia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
0
5
0
5
Order By: Relevance
“…Three of four peer‐reviewed documents had lower methodological quality, meeting one or two out of five MMAT quality criteria 39–41 . The remaining study met three out of five criteria, indicating higher quality 42 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of four peer‐reviewed documents had lower methodological quality, meeting one or two out of five MMAT quality criteria 39–41 . The remaining study met three out of five criteria, indicating higher quality 42 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…One grey literature 53 record reported the largest amount saved (AUD 50000/year) from reduced hauling fees, while another 64 reported the smallest saving, (AUD 383/month) achieved by removing a rented dumpster that was no longer needed. Several records ( n = 10) 39,43,56,57,59,61,65,67–69 also reported the costs of setting up or implementing a food or food‐related waste management strategy. The largest cost (AUD 260538) was for setting up dehydrators 67 and the smallest cost (AUD 1243/year) was for food waste collection by a composting company 56…”
Section: Resultsmentioning
confidence: 99%
“…The area for biodigester implementation must be considered despite having a low percentage (10.36%) compared to the machinery group, as if it is not used for this purpose, it could be used for another productive activity. Amounts and percentages invested in biodigester implantation could not be compared with the few studies found in the literature (Lima & Miranda, 2014;Nascimento et al, 2017;Westrup et al, 2015) since these did not detail the investment division. Moreover, most of the studies did not adopt a solid separator machine, which features a different production system with lower investments.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the importance of the power generation sector, several researchers have assessed the economic viability of alternative sources. Among these initiatives are studies on the production of microalgae for power production (Holanda & Ramos, 2011); use of biogas in pig farms (Lima & Miranda, 2014;Martins & Oliveira, 2011;Westrup et al, 2015); potential and economic/ environmental viability of biodigesters in a hospital environment (Nascimento, Maia, Silva, & Santos, 2017); use of tidal power (Bispo et al, 2016); power production costs using biogas from manures of goat, cattle, and pig in semi-confinement systems (Calza, Lima, Nogueira, Siqueira, & Santos, 2015); the economic viability of biogas from pig farming for power generation (Cervi, Esperancini, & Bueno, 2010); biodigestion and biogas production using bovine manure (Dotto & Wolff, 2012); anaerobic biodigestion economic analysis in beef cattle farming (Montoro, Santos, & Lucas, 2013); and anaerobic biodigestion in pig farming (Rizzoni, Tobias, Bianchi, & Garcia, 2012). However, only one study on the viability of generating power using biogas on dairy farming has been found (Coldebella, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…con características en la concentración de la materia prima (tabla 1). El trabajo fue realizado tomando como referencia el estudio realizado por Do Nascimento y colaboradores, en el que analizó la generación de energía eléctrica y viabilidad técnico-económica de un biodigestor en el sector hospitalario (10).…”
Section: Materiales Y Metodosunclassified